Analisis Penerimaan Konsumen Terhadap Jambu Jelly Drink dengan Penambahan Bayam: Analysis of The Acceptance of Jambu Jelly Drink with The Addition Of Spinach - Assegaf, Safira; Purnaningsih, Sri; Alasimi, Nadina (Jurnal Teknologi dan Mutu Pangan, 2025)
Indonesia as a tropical country has abundant availability of jambu raw materials, thus enabling the development of this product sustainably while supporting the empowerment of local farmers. By being packaged as a healthy and innovative product, jambu jelly drink can contribute to meeting the needs of the domestic and global markets with the addition of spinach, but consumer acceptance of this new product still needs to be analyzed. This study aims to analyze consumer acceptance of jambu jelly drink with added spinach. The method used in this study is the Hedonic Test which includes sensory aspects, including taste, aroma, color, and texture. A total of 30 respondents participated in the sensory evaluation using a structured questionnaire. The results showed that the average scores for taste (4.2) and texture (4.1) were very positive, indicating strong consumer preference. However, the average score for color (3.8) showed less desirable results. Inferential statistical analysis using the t-test showed significant differences between the acceptability of taste and color (p < 0.01) and aroma and color (p < 0.05), indicating that consumers prioritized taste over visual appeal. These findings highlight the potential of guava jelly beverage as a nutritious drink, while indicating the need to improve its visual attributes to increase market acceptance. This study contributes to the development of functional beverages by integrating natural ingredients, which promote health benefits and sensory enjoyment.